A planície costeira do Amapá: dinâmica de ambiente costeiro influenciado por grandes fontes fluviais quaternárias - SILVEIRA, Odete Fátima Machado da (Universidade Federal do Pará, 2017)
The Amapá State is located at the extreme north of Brazil. The geographic boundaries are The French Guyana (N); The Pará State (W and S), and the Atlantic Ocean to the east. The Amapá coastal plain comprises more than 300 Km of sediments deposited from the north of Amazon river through the Cabo orange, at the extreme north of the Amapá State. It reaches 120 Km width near Cabo Norte and becomes near 10 Km width near Cunani, enlarging again through the Cabo Orange. The aim of this research was to understand how the structural arcabouce and the sea level changes conditionated the development of holocenic deposits and the consequent coastal plain evolution. The Amapá Coastal Plain is inserted into the Amazon River Mouth Sedimentary Basin which is characterized by two grabens (Limoeiro e Mexiana) and two platforms, Pará e Amapá, respectively. The structural elements has an deep relation with the drainage network and throughout them and them behaviour, it was possible the identification of neotectonic records. As a low gradient region, the drainage net answered to the pressures exerted by this factors, becaming an important tool to evaluate the morphological changes ocurred during the geologic time. At the Amapá coastal plain it was possible to identify both, an actual an a paleodrainage net as well. The phisiographic and morphological characteristics of the Amapá coastal plain are defined by the regional structural arcabouce. Two phases of development were considered: 1) Pre-Holocenic Phase; 2) Holocenic Phase. The alluvial processes and the relative sea level positions contributed to the coastal plain remodelling. The re-arrangement aí the drainages to the actual layout is related to the neotectonic processes ocurred after Barreiras Group deposition which probably is still acting. Two morphological domains were defined to the Amapá coastal plain by BOAVENTURA & NARITA (1974): The north domain shows the predominance of marine processes while the south domain is influenced mainly by fluvial processes. The oceanographic and atmospheric parameters (tides, currents and trade winds) ocurring at the Amazon Shelf exerts a clear effect at the coastline, and the morphology, determined by the tectonic arcabouce propitiate the erosional and deposítional processes, depending of it relative position to the regional base level. The relative sea level position during the Holocene did play an important role on the Amapá coastal plain evolution. The sea levels position were recorded throughout the Calçoene Chenier Plain and the Cunãni-Cassiporé Chenier Plain which evolution are deeply related to the Cabo Cassiporé built process.